Use of Continuous-Wave Doppler Echocardiography to Evaluate the Hemodynamic Importance of Atrial Systole in Patients with Mitral Stenosis - Stojnic, Bojan (1990)
Continuous-wave Doppler echocardiography was used to assess the hemodynamic role of left atrial systole and its effect on left ventricular performance in 31 patients with pure mitral stenosis. Seventeen (group I) had severe stenosis, and 14 (group II) had mild-to-moderate stenosis. The contribution of atrial systole to cardiac output was 15% in group I and 24% in group II (p < 0.01). This study shows the effectiveness of using continuous-wave Doppler echocardiography to assess the influence of atrial systole on left ventricular performance in patients with mitral stenosis. (Texas Heart Institute Journal 1990;17:219-22)